The Peculiarities Of Neologizms In Language And Speech - Kukiboyeva, Mahliyo; Rakhimova, Nasiba (Indonesian Journal Publisher, 2024)
Language is a dynamic, evolving process that reflects the ever-changing realities faced by its speakers. One of the key factors driving this linguistic evolution is the creation of neologisms—new words or expressions that emerge to fill gaps in language or express new concepts, often as a response to technological advancements, cultural shifts, and globalization. Neologisms not only enrich the vocabulary but also offer a rich point of analysis in linguistics, shedding light on societal and cultural contexts. They are formed through various processes such as borrowing, compounding, blending, and acronym creation, all of which reflect the interaction between linguistic mechanisms and the cultural environment. This paper explores the formation and implications of neologisms from both linguistic and cultural perspectives, with a particular focus on ecolinguistics and sociolinguistics. Historical examples, such as the Industrial Revolution and the Digital Era, illustrate the deep connection between language and social change. By examining neologisms, this study seeks to illuminate the role of language in adapting to societal transformations and how it serves as both a mirror and a driver of cultural evolution.